Revision of the Schistura cincticauda species group (Teleostei, Nemacheilidae) using molecular and morphological markers - Dvořák, Tomáš; Bohlen, Jörg; Kottelat, Maurice; Šlechtová, Vendula (Scientific reports, 2023)
To approach the taxonomy of large and complex animal groups it is of advantage to focus on species groups with shared derived character state. We investigate the composition, morphological characteristics and relationships of and within the Schistura cincticauda species group, whose members are small freshwater fishes that inhabit streams and rivers in eastern Myanmar and western and southern Thailand. A phylogenetic analysis using molecular genetic markers demonstrated the monophyly of this group; a combined genetic and morphological analysis revealed the inclusion of at least twelve species. They share the presence of a pair of black marks on the lower lip, one on each side of the median interruption (these marks may be reduced to few melanophores or even missing in some individuals). Additionally, all species share a small body size (max. 60 mm SL), an incomplete lateral line reaching at most to vertical through anal-fin base, and the absence of sexual dimorphism. Each of the 12 species is diagnosed by a unique combination of character states in fin ray numbers, anus position, presence/absence of an axillary pelvic lobe, and colour pattern. The distribution areas of several species overlap and five cases of syntopic occurrence are known. Five unnamed species are described herein.
Keywords: Cypriniformes; Phylogeny; řeky; velikost těla; máloostní; Animals; lidé; Rivers; Body Size; pohlavní dimorfismus; Sex Characteristics; Humans; zvířata; fylogeneze